From Local Niche To Global Market: Internationalization Process And Strategic Capabilities Of Indonesian Smes Evidence From Sensatia Botanicals - Indriani Detty Permatasari; Sudarmiatin; Heri Pratikto (International Journal of Business and Quality Research, 2026)
The internationalization of micro, small, and medium-sized enterprises (MSMEs) is a strategic issue in the global economic landscape, particularly in developing countries like Indonesia, which face the challenge of limited resources yet vast market potential. This case study explores the internationalization process of Sensatia Botanicals, an MSME specializing in skincare products made from natural botanical ingredients based in Jasri, Karangasem, Bali, which was founded in 2000. A qualitative single-case study approach adopts the Uppsala Internationalization Model integrated with the Resource-Based View (RBV) to analyze the stages of expansion: beginning with experimental exports to the Southeast Asian market (2010–2015), acceleration through global e-commerce platforms such as Amazon, Shopee International, and Lazada Global (2016–2020), to deep penetration via distribution partnerships in Europe (Germany, the Netherlands) and North America (2021–present), with exports contributing 40% of the latest annual revenue of Rp 150 billion (2024). The company’s dynamic strategic capabilities include product innovation based on local Balinese resources (such as frangipani and organic turmeric), a commitment to sustainability (zero-waste production using 90% local materials), ethical practices (fair trade with over 500 local farmers), and a portfolio of more than 200 internationally certified product variants, including GMP, MUI Halal, ECOCERT, and USDA Organic—all completely free of parabens, palm oil, and harmful synthetic ingredients. Major challenges such as export regulatory uncertainty, rupiah exchange rate volatility, and competition from global brands (such as The Body Shop or Lush) were successfully navigated through a phased learning strategy, strategic alliances with global suppliers, and AI-driven digital transformation for customer personalization. Findings also indicate that integrating local capabilities (Bali’s unique botanicals) with global adaptation (international certifications and digital agility) yields a sustainable competitive advantage, with international customer retention rates reaching 70% (based on 2023–2024 CRM data), post-pandemic annual export growth averaging 28%, and expansion into 35 countries with over 15,000 global retail stores. This research makes a theoretical contribution by extending the Uppsala model through the lens of dynamic capabilities in the context of emerging market SMEs, while also providing managerial implications for Indonesian SME practitioners in building global competitiveness. Furthermore, from a management education perspective, these findings are relevant for the development of doctoral curricula that integrate real-world case studies of internationalization